Comparative Molecular Study between Some Plant Extract and Tinidazole of Hydatid cysts in Basrah, Southern Iraq - Jalal Y. Mustafa1, Ghazi Y. Azzal1, Suzan A. Al-Azizz1, Fatin A. Muatafa2, Arwa R. Lazim2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Hydatid disease or Echinoccosis is one of the serious public health problems. This study was designed as a comparative molecular study between some plant extract and tinidazole of sheep hydatid cysts in Basrah province. In this study, 213 sheep were examined and the number of those infected with hydatid cysts was 75 (35.2 %). The results showed that hydatid cyst were detected successfully by performing PCR technique. In addition, Quercus aegilops has been shown the best plant extract for destroying all genes, the second plant extract which is Capparis spinosa showed destroying of two genes (G6-7, COI) and failed to destroy (sh4-1). Furthermore Prosopis fracta has showen to destroy only (G6-7) and tinidazole failed to destroy any of these genes used in this study.